Titanium dioxide - activated carbon composite for photoelectrochemical degradation of phenol - L. H. Q. Anh; Uyen P. N. Tran; P. V. G. Nghi; H. T. Le; N. T. B. Khuyen; T. D. Hai (Chimica Techno Acta)
In this study, titanium dioxide (TiO2) and titanium dioxide – activated carbon composite (TiO2–AC) were prepared by sol-gel method for photoelectrochemical (PEC) applications. Characterization of the materials was performed by scanning electron microscope, energy dispersive X-ray analysis, Fourier transform infrared spectroscopy, X-ray diffraction, and diffuse reflectance spectroscopy. The results show that TiO2 was successfully loaded on activated carbon (AC), producing TiO2–AC with 2.61 eV of bandgap energy, lower than that of TiO2 (3.15 eV). Photoanodes based on TiO2 and TiO2–AC were fabricated and applied to PEC experiments for phenol degradation. In comparison with the TiO2 photoanode, the TiO2–AC one exhibited superior photocatalytic activity, which was indicated by a high current density and effective phenol removal. A mechanism of phenol PEC degradation on the TiO2–AC photoanode was proposed, which includes interaction between protonated phenol and active sites bearing oxygen on the photoanode surface. A kinetic model according to this mechanism was also established and fitted to experimental findings, resulting in rate constants of elementary reactions.